Fatalitas dan analisis apasial lokasi rawan kcelakaan lalu lintas di kabupaten Gunungkidul - Aning Isfandyari; Lutfan Lazuardi (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Fatality and spatial analysis of road traffic accident in Gunung KidulPurposeThis study is aimed to conduct further analysis of road accidents fatality and accident-potential area using geographic information system.MethodsThis was an analytic observational study using cross-sectional study design. Samples are all traffic accident recorded in police departement accident registry from January 1st to December 31st 2015. Data will be analyzed using poisson regression with robust variance and accident location will be analyzed spatially using ArcGIS 10.4 software.ResultsThe result revealed that 06.00-11.59 a.m (PR 0.31, 95% CI 0.144-0.687) or 12.00-17.59 p.m (PR 0.40; 95% CI 0.184-0.865), uphill roadway geometric (PR 2.16, 95% CI 1.144-4.094) or winding roadway (PR 1.80, 95% CI 1.013-3.213) and single accident type (PR 3.59; 95% CI 1.953-6.592) were significant factors affecting road traffic fatalities. Accident-prone locations to traffic accidents in Gunungkidul are clustered on several streets, such as Yogyakarta-Wonosari Street, Karangmojo-Semin Road, Wonosari Semanu Street and Wonosari Baron Street..ConclusionsFatal traffic accident in Gunungkidul are influenced by environmental conditions and accident types. Multisectoral coordination was needed to improve intervention to population at risk and stakeholders need to make efforts to modify the environment related to road geometric conditions to minimize the occurrence of accidents.